2021
DOI: 10.1002/asi.24595
|View full text |Cite
|
Sign up to set email alerts
|

Information behavior patterns: A new theoretical perspective from an empirical study of naturalistic information acquisition

Abstract: This empirical study offers a new theoretical perspective in information behavior research by identifying interrelationships between certain information behaviors. While previous work recognizes the iterative nature of information acquisition, information behavior research has so far been dominated by the identification and conceptual elaboration of discrete behaviors. We introduce the theoretical concept of 'information behavior patterns' to characterize the intricate connectedness of information interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The importance of passive information encountering has been highlighted in previous studies, which have found that people do not always actively seek information; sometimes they passively encounter it (e.g., Lee et al, 2022; Yadamsuren & Erdelez, 2016). However, what is particularly salient about these findings is that passive encounters were the primary way people became aware of the potential to change their views.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of passive information encountering has been highlighted in previous studies, which have found that people do not always actively seek information; sometimes they passively encounter it (e.g., Lee et al, 2022; Yadamsuren & Erdelez, 2016). However, what is particularly salient about these findings is that passive encounters were the primary way people became aware of the potential to change their views.…”
Section: Resultsmentioning
confidence: 99%
“…Salmon's five-stage eregulation model (da Gama Silva et al, 2019;Motaung and Makombe, 2021), Learning Design Sequence model (Hrastinski, 2020;Reyna, 2020), and design for learning model (Dickinson and Gronseth, 2020;Rabinowitz and Tondreau, 2022) are preferred in digital environments. In using knowledge in digital environments dimensions, information behavior (Kurniasih, 2019;Lee et al, 2022;Yavetz and Aharony, 2022) and digital literacy (Baterna et al, 2020;Barnes and Potter, 2021;Çetin, 2021) theorical framework are applied.…”
Section: Discussionmentioning
confidence: 99%
“…As we progress through the information age, with increasing levels of information and technology ubiquity, we now interact with a far richer and more complex information landscape than we once did (Bawden and Robinson, 2008) and appreciate both a broader range and more complex nuance of information behavior within it (Lee et al, 2022). For example, the prevalence and wide availability of online news has increased the possibility of coming across news incidentally, during other activities.…”
Section: Introductionmentioning
confidence: 99%